Isolated Dipolar ONN Schiff Base Regioisomers: Synthesis, Characterization and Crystallographic Study - Pablo Castro-Tamay; David Villaman; Jean-René Hamon; Néstor Novoa (Molecules)
Organic compounds with 1,3-diketone or 3-amino enone functional groups are extremely important as they can be converted into a plethora of carbo- or heterocyclic derivatives or can be used as ligands in the formation of metal complexes. Here, we have achieved the preparation of a series of non-symmetrical β-ketoenamines (O,N,N proligand) of the type (4-MeOC6H4)C(=O)CH=C(R)NH(Q) obtained through the Schiff base condensation of 1,3-diketones (1-anisoylacetone, 1-anisyl-3-(4-cyanophenyl)-1,3-propanedione, and 1-anisyl-3-(4,4,4-trifluorotolyl)-1,3-propanedione) functionalized with electron donor and electron-withdrawing substituents and 8-aminoquinoline (R = CH3, 4-C6H4CN, 4-C6H4CF3; Q = C9H7N). Schiff base ketoimines with a pendant quinolyl moiety were isolated as single regioisomers in yields of 22–56% and characterized with FT-IR, 1H NMR, and UV-visible spectroscopy, as well as single-crystal X-ray crystallography, which allowed for the elucidation of the nature of the isolated regioisomers. The regioselectivity of the condensation of electronically unsymmetrical 1,3-diaryl-1,3-diketones with 8-aminoquinoline was studied by 1H NMR, providing regioisomer ratios of ~3:1 and ~2:1 in the case of CN and CF3 substituents, respectively. The electronic effects correlate well with the difference between the Hammett σ+ coefficients of the two para substituents on the aryl rings.